Bibliometric Analysis of Mobile Payment Technology Innovation in Financial Transaction Transformation - Eva Yuniarti Utami; Halek Mu'min; Agung Zulfikri (Westscience Press, 2024)
Mobile payment technology has become increasingly prevalent, reshaping the landscape of financial transactions globally. This study conducts a comprehensive bibliometric analysis to explore the trends, patterns, and dynamics surrounding mobile payment technology innovation. Through systematic data collection and analysis, key themes, influential authors, pivotal publications, and emerging topics in the field are identified and examined. The analysis reveals the transformative impact of mobile payment technology on financial systems, consumer behavior, and business models. Moreover, it underscores the significance of understanding the underlying factors influencing innovation in this domain. The findings provide valuable insights for researchers, policymakers, industry practitioners, and consumers, informing strategic decision-making and technological development efforts in the financial and technology sectors.